2023
DOI: 10.1371/journal.pone.0274679
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of green synthesized selenium nanoparticles and their effect on physiological, biochemical, and antioxidant defense system of mango under mango malformation disease

Abstract: Plant extract-based green synthesis of nanoparticles is an emerging class of nanotechnology that has revolutionized the entire field of biological sciences. Green synthesized nanoparticles are used as super-growth promoters and antifungal agents. In this study, selenium nanoparticles (SeNPs) were synthesized using Melia azedarach leaves extract as the main reducing and stabilizing agent and characterized by UV–visible spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), energy-dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 116 publications
(154 reference statements)
1
17
0
Order By: Relevance
“…Shahbaz et al reported the foliar-applied Se at 30 μg/mL increased the shoot content of superoxide dismutase (SOD) and peroxidase (POD) in mango by 1.07-and 4.63-fold, respectively, as compared to Fusarium-infected control, resulting in a greater tolerance biotic stress. 23 Conversely, we found the opposite results in the infected and untreated roots, where the ROS level was much lower than that of all the other treatments (Figure 2D). This may be due to significant cell death and, thus, no active ROS accumulation at this stage of Fusarium infection.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Shahbaz et al reported the foliar-applied Se at 30 μg/mL increased the shoot content of superoxide dismutase (SOD) and peroxidase (POD) in mango by 1.07-and 4.63-fold, respectively, as compared to Fusarium-infected control, resulting in a greater tolerance biotic stress. 23 Conversely, we found the opposite results in the infected and untreated roots, where the ROS level was much lower than that of all the other treatments (Figure 2D). This may be due to significant cell death and, thus, no active ROS accumulation at this stage of Fusarium infection.…”
Section: Resultsmentioning
confidence: 97%
“…Se plays an important role in protecting plants from oxidative stresses by enhancing the activity of enzymatic antioxidants. Shahbaz et al reported the foliar-applied Se at 30 μg/mL increased the shoot content of superoxide dismutase (SOD) and peroxidase (POD) in mango by 1.07- and 4.63-fold, respectively, as compared to Fusarium -infected control, resulting in a greater tolerance biotic stress . Conversely, we found the opposite results in the infected and untreated roots, where the ROS level was much lower than that of all the other treatments (Figure D).…”
Section: Effects Of Se Nps On Lettuce Growthmentioning
confidence: 99%
“…The responses and genetic damage of NPs inside a system are determined by the agglomeration process [132]. Nevertheless, when particles are not organized into agglomerates, they can disperse themselves, thereby enhancing the formation of reactive oxygen species (ROS) formation [133]. In addition, the surface charge of the material plays a crucial role.…”
Section: Antifungal Mechanism Of Fe Npsmentioning
confidence: 99%
“…Table (2) shows the effect of Se-NPs and Se-Nps + D3 in immunosuppressed rats on the activity of liver enzymes. The results showed that the activity of AST, ALT, and ALP enzymes increased significantly at (P<0.05) in the group of experimentally immunosuppressed animals (T2) at 52, 62.66, and 411, respectively, compared with the group of healthy control animals (T1), which were at 35.66 and 39. and 208.66, respectively.…”
Section: Effect Of Se-nps and Se-nps + D3 In Immunosuppressed Rats Gi...mentioning
confidence: 99%